Evaluating mucoadhesion properties of three types of nanocellulose in the gastrointestinal tract in vitro and ex vivo. (15th April 2019) - Lin, Yu-Ju; Shatkin, Jo Anne; Kong, Fanbin
Graphical abstract: Highlights: Nanocellulose retains on both porcine stomach and small intestinal mucosa ex vivo . Nanocellulose shows viscosity synergism with porcine mucin in GI condition in vitro . CNC interacts with mucin molecules and changes the zeta potential of mucin. Abstract: The mucoadhesive properties of three types of nanocellulose (CNF, CNC, and Tempo-CNF) was investigated in the digestive condition with ex vivo and in vitro assays. In the ex vivo flow-through method, three nanocellulose materials showed different levels of retention on porcine gastric and intestinal mucosal surfaces. Fluorescence microscopy confirmed that retention of CNF could be due to entanglement with the mucosal layer, while retention of Tempo-CNF could be due to instantaneous gelling on the mucosal surface. In an in vitro viscometric method, 2% CNC showed the highest viscosity synergism (relative enhancement=11.80 ± 1.14) in the gastric condition, while Tempo-CNF only displayed synergism under gelling concentrations (0.1%). Evaluation of zeta potential revealed that 0.025–0.1% CNC interacted with mucin particles by changing the surface charge of the mucin-nanocellulose system. These results indicate that nanocellulose shows mucoadhesive properties in digestive tract, where the level of adhesion depends on type of nanocellulose, its concentration and the gastrointestinal section.